ҚҰРАҚСУ КӨЛДЕРІНІҢ ҚАЗІРГІ КЕЗДЕГІ ИХТИОФАУНАСЫНЫҢ ҚҰРАМЫ (АҚСУ ӨЗЕНІ, БАЛҚАШ КӨЛІ БАССЕЙНІ) (Experimental biology, 2015)
The chain of the lakes Kuraksu includes the of lakes Rai, Baklan, Sarykol and Kokyshkol, which are located consistently on either side of a mouth of river Aksu (basin lake Balkhash), Aksu region, Almaty area. All lakes closed, are located about the right and is left from the river on distance approximately from 2-3 to 5-6 km. To the greatest among them is lake Baklan. Results of researches spent in 2010 have shown to the chain of the lakes Kuraksu, that 10 kinds of fishes, appurtenant to 4 families of following groups - cypriniformes, siluriformes, cyprinodontiformes and perciformes there live. The basic part fish fauna was made by fishes a Caspian roach (Rutilus rutilus caspicus), a carp (Cyprinus carpio carpio) and a pike perch (Sander lucioperca).The biological analysis of trade kinds of fishes, including dimensional, weight, age, sexual characteristics which testify to favorable conditions of dwelling hydrobionts is carried out. In the investigated reservoirs in spring spawning the period on result haul minnow seine natural reproduction of populations of fishes is studied. Also it is considered fish capacity the chain of the lakes Kuraksu. and the greatest fish capacity characterises lake Baklan. After the surveyed lakes fish capacity lake Baklan it has appeared above.With a view of increase fish capacity internal reservoirs of local value the scientifically-proved recommendations about rational use of food fishes are given.
Keywords: lakes Kuraksu